(untitled) (Journal of the College of Languages (JCL), 2005)
This research deals with number of novels for Marguerit Doras , specially A Bridge Towards Basfic and The Lover . we specialize the first chapter for discussing a very important issue , which is the Maraguerit Doras novelist world in another word the most important themes . that we discuss and through that we tried to clerify the privacy the characters of Marguerit Doras in comparative with her own generation and in the second chapter we discussed the most important characteristics of the romantic hero spedially the characteristics of women in her novels.